2022
DOI: 10.1097/icu.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

Corneal hysteresis: ready for prime time?

Abstract: Purpose of the reviewThis review summarizes recent findings on corneal hysteresis, a biomechanical property of the cornea. Corneal hysteresis measurements can be easily acquired clinically and may serve as surrogate markers for biomechanical properties of tissues in the back of the eye, like the lamina cribrosa and peripapillary sclera, which may be related to the susceptibility to glaucomatous damage.Recent findingsSeveral studies have provided evidence of the associations between corneal hysteresis and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…It is, therefore, believed that the greater the value of this shock absorption or hysteresis, the greater the intrinsic ability of the ocular structures to deal with applied force or stress and, therefore, the lower the likelihood of nerve damage due to increased strain on the optic nerve head in the area of the lamina cribosa. Numerous studies have demonstrated that eyes with lower hysteresis values had faster rates of visual field loss than those with higher hysteresis values [ 37 , 38 , 39 ]. Corneal hysteresis may be a surrogate marker for hysteresis values elsewhere, specifically in the peripapillary sclera and the trabecular meshwork.…”
Section: Hysteresis and The Corneamentioning
confidence: 99%
“…It is, therefore, believed that the greater the value of this shock absorption or hysteresis, the greater the intrinsic ability of the ocular structures to deal with applied force or stress and, therefore, the lower the likelihood of nerve damage due to increased strain on the optic nerve head in the area of the lamina cribosa. Numerous studies have demonstrated that eyes with lower hysteresis values had faster rates of visual field loss than those with higher hysteresis values [ 37 , 38 , 39 ]. Corneal hysteresis may be a surrogate marker for hysteresis values elsewhere, specifically in the peripapillary sclera and the trabecular meshwork.…”
Section: Hysteresis and The Corneamentioning
confidence: 99%
“…[11][12][13] Otherwise, several studies have suggested that patients with ocular hypertension (OHT) but no glaucomatous changes showed less deformable corneas. 9,10,[14][15][16] These corneal biomechanical differences indicate that the appearance and progression of glaucoma could be associated with specific corneal biomechanical DOI: 10.1097/IJG.0000000000002170 changes, 17,18 which may offer a novel perspective on glaucoma pathology.…”
mentioning
confidence: 99%
“…70,71 Eyes with lower corneal hysteresis may also have lower scleral hysteresis, which in turn may render them poorer at dissipating the mechanical stress from IOP. 72 Given that reduced biomechanical resistance of the sclera has been implicated in PM, 73 elevated IOP could plausibly be associated with increased PM susceptibility by virtue of its correlation with reduced scleral hysteresis. An alternative theoretical framework put forth by Wang et al 74 points towards increased activation of scleral fibroblasts leading to increased scleral remodelling and reduced choroidal perfusion in response to elevated IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal hysteresis (viscoelasticity) is known to decrease with increasing levels of myopia 67–69 and IOP 70,71 . Eyes with lower corneal hysteresis may also have lower scleral hysteresis, which in turn may render them poorer at dissipating the mechanical stress from IOP 72 . Given that reduced biomechanical resistance of the sclera has been implicated in PM, 73 elevated IOP could plausibly be associated with increased PM susceptibility by virtue of its correlation with reduced scleral hysteresis.…”
Section: Discussionmentioning
confidence: 99%